A two‐turn loop active magnetic field probe design for high sensitivity near‐field measurement. Issue 1 (3rd October 2021) - Shao, Weiheng; Li, Jianke; Huang, Quan; Shao, E; Liu, Jiesheng; He, Xiao; Yi, Zhiqiang; Fang, Wenxiao; Zhou, Changjian
Abstract: This paper develops an active magnetic near field probe (H‐field probe) by using a four‐layer printed circuit board (PCB) technique. Two‐turn detection structure and a low noise amplifier are used to improve probe's frequency response. The two‐turn detection structure can maximize the use of PCB stack resources, and a 14.5 dB gain amplifier can increase signal output capability. The probe can then be used for electromagnetic compatibility (EMC) test from 150 kHz to 3 GHz. Compared with traditional active shielded‐loop H‐field probe (TAHP) with loop area of 500 μ m 2, the frequency response of the proposed probe can improve 20 dB at 0.5 GHz. Different from the method of comparing the sensitivity of the probe only through the frequency response, this paper measures and analyzes the real sensitivity of the probing device composed of the proposed probe. Under the condition of the same receiver parameter setting, the sensitivity at 0.5 GHz is increased by 11.7 dB compared with commercial passive probing device and 20.2 dB at 0.5 GHz compared with the probing device with TAHP device. It reaches −32.4 dB μA. In addition, the proposed probe has acceptable spatial resolution of 1.28 mm at 1 GHz, which is more suitable for printed circuit board level EMI analysis.